The strategy of Japanese business - Abegglen, James C. (Ballinger Pub. Co., 1984)
Based on a survey we conducted with sales departments of major manufacturing companies in Japan, this paper will discuss what exactly an excellent competitive strategy is in relation to the "competitive domain." Our task is to answer such questions as: Is there a single best strategy? If so, what is it? If not, how and when must the strategy be changed as circumstances vary? To begin, let us introduce our survey-based analytical approach.